Unstratified systematic sampling: Rationale and method - Norton-Griffiths, M. (International Livestock Centre for Africa, 1981)
Discusses techniques of unstratified systematic sampling for collecting baseline data on animal numbers and distributions and for monitoring through time the changes in patterns of distribution and their relationships to biotic and abiotic features of the environment, compares the relative strengths and weaknesses of the method with those of stratified random sampling.